Timing is everything : photoperiodicity shaping life-history traits and gene expression - Salminen, Tiina S. (2011)
The effects of photoperiodic cues on the timing and shaping of life-history traits in northern latitude species are vast. In my doctoral thesis, I have studied the factors affecting the ability of Drosophila virilis group flies (mainly D. montana) to survive in northern latitudes with high seasonal and daily variation in environmental conditions. This was done by studying the role of photoperiod and temperature cues in evoking changes in reproductive diapause and other life-history traits important in adaptation to a seasonally varying environment, as well as by studying the expression patterns of genes affecting these traits. The main findings were that photoperiodic cues can induce changes in life-history traits at both pre (egg-to-eclosion development time and juvenile body mass) and post (reproductive diapause) eclosion stages. Measuring the day length and adjustment of life-history traits can be restarted after eclosion, which enables the flies to react quickly and optimally to changing photoperiods at different developmental stages. The sensitive period for induction of reproductive diapause was found to be temperature-dependent and connected to the enhanced rate of ovarian development in higher temperatures. When the females were able to detect both photo- and thermoperiods mimicking seasonal variation of their natural habitat, the seasonal switch to diapause happened within a remarkably short time window. The correct timing of this switch, as well as the environmental conditions that the females are experiencing during young adulthood, was found to have an effect also later in life as the effects of diapause was still seen e.g. in cold tolerance levels, after diapause was terminated as well as in the gene expression patterns.